Entrepreneurship policy: issues and challenges. Issue 3 (1st September 2016) - Smallbone, David
ABSTRACT: This article explores some current issues concerning entrepreneurship policy. It begins by examining the case for and against entrepreneurship policy followed by an analysis of the following issues: (1) the importance of context, which refers to the circumstances in which the policy was introduced and possibly maintained or modified; (2) the need for both researchers and practitioners to pay more explicit attention to the policy process which includes policy formulation, implementation, monitoring and evaluation; (3) the call for evidence-based policy in which it is suggested that what constitutes evidence is not always agreed between researchers, practitioners and policy-makers; (4) the need for a strengthened commitment to policy evaluation and (5) public procurement as an under-utilized type of policy intervention, yet one which is potentially very powerful.